Tax impact of the rental fee for squares and markets in the Ambato canton in times of COVID - 19 - Salazar Mejía, César (2021)
The study determines the tax impact of the rental fee for squares and markets in the canton of Ambato in times of COVID-19. The inadequate establishment of rental values, the inefficient determination of the taxable liquid for its collection and the pandemic is what has impacted the successful tenderers and mainly from the perspective of the municipality with regard to the issuance of lease titles of the network of squares and markets has implied a decrease in their income. For the analysis, we worked with research from secondary sources available in databases and reports of the Autonomous Decentralized Government of the Municipality of Ambato as well as the official Register of the Government of Ecuador, the Commonwealth Agreement and Municipal Ordinances. According to the results obtained, it is concluded that the GADMA has a tax impact of 52% less than the total taxable liquid in the year 2020. Additionally, based on the exploration of the aforementioned central problem, it is stated that the taxable liquid regarding the lease fee that actually exists has not been determined. URL: https://revistas.uta.edu.ec/erevista/index.php/bcoyu/article/view/1409